UANG DIGITAL LITECOIN PERSPEKTIF HUKUM ISLAM - Nurul Huda, Siti; Ihwanudin, Nandang (Asosiasi Dosen PTKIS Indonesia, 2023)
This study aims to determine the law of using Litecoin digital money from an Islamicperspective. The research method used is descriptive method and content analysis. The results of the studyshow that the use of litecoin digital money according to an Islamic view is the same as buying and sellingmoney with money or in fiqh muamalah terms it is called al-sharf, so it is only natural that according tothe MUI fatwa Number: 28/DSn-MUI/III/2002, rules regarding buying and selling have beenestablished. money in the fatwa which reads: Currency buying and selling transactions are in principlepermissible, with the following conditions: Not for speculation (coincidence), there is a transaction needor for precaution (savings), If the transaction is carried out in the same currency, the value must be thesame and in cash (attaqbudh). If it is of a different type, it must be made at the exchange rate (rate)valid at the time the transaction was made and in cash. The mechanism for using Litecoin digital moneyin buying and selling transactions already has conditions and rules that must be met, which are far fromgharar (obscurity), because Litecoin is purely evil in nature (unknown). and demands. this is whatmakes this practice contain maesar. Because there is speculation seeking profit, and trying their luck.Will sell when the price goes up, and sometimes the value can drop to zero. even though in Islam there isno stipulation that money must be in the form of gold and silver, then as an object digital money litecoinis permissible. However, in practice it contains unclear elements and seeks profit by exploiting pricefluctuations that are not in accordance with Islamic law. So, using Litecoin digital money is notrecommended because it has disadvantages for users.